The therapeutic concordance approach reduces adverse drug reactions in patients with resistant hypertension - Trimarco, Valentina; Manzi, Maria Virginia; Izzo, Raffaele; Mone, Pasquale; Lembo, Maria; Pacella, Daniela; Esposito, Giovanni; Falco, Angela; Morisco, Carmine; Gallo, Paola; Santulli, Gaetano; Trimarco, Bruno (Frontiers in Cardiovascular Medicine, 2023)
Background Adverse drug reactions (ADRs) remain among the leading causes of therapy-resistant hypertension (TRH) and uncontrolled blood pressure (BP). We have recently reported beneficial results in BP control in patients with TRH adopting an innovative approach, defined as therapeutic concordance, in which trained physicians and pharmacists reach a concordance with patients to make them more involved in the therapeutic decision-making process. Methods The main scope of this study was to investigate whether the therapeutic concordance approach could lead to a reduction in ADR occurrence in TRH patients. The study was performed in a large population of hypertensive subjects of the Campania Salute Network in Italy (ClinicalTrials.gov Identifier: NCT02211365). Results We enrolled 4,943 patients who were firstly followed-up for 77.64 ± 34.44 months, allowing us to identify 564 subjects with TRH. Then, 282 of these patients agreed to participate in an investigation to test the impact of the therapeutic concordance approach on ADRs. At the end of this investigation, which had a follow-up of 91.91 ± 54.7 months, 213 patients (75.5%) remained uncontrolled while 69 patients (24.5%, p < 0.0001) reached an optimal BP control. Strikingly, during the first follow-up, patients had complained of a total of 194 ADRs, with an occurrence rate of 68.1% and the therapeutic concordance approach significantly reduced ADRs to 72 (25.5%). Conclusion Our findings indicate that the therapeutic concordance approach significantly reduces ADRs in TRH patients.